Integrated marketing communication as a business management tool in the context of sustainable development - Daina Šķiltere; Santa Bormane (Open Economics, 2018)
The problem of nowadays is that consumers lack information on food products, their composition and quality, nutritional value, packaging, its impact on the human health and environment, reuse and recycling possibilities, etc. Integrated marketing communications (IMC) as a business management tool may not only draw the consumers' attention and incite a purchase, but also provide information and serve as a facilitator of consumers' knowledge and competence on products, their nutritional value, use and utilisation. The goal of the research is to assess the impact of IMC for sustainability upon demand at Latvian food retail chains and the impact of the use of IMC for sustainability upon sustainable development. The object of the research is Latvian food retail chains, and the subject of the research is the use of IMC for sustainable development. The authors in 2017 surveyed leading specialists from food retail chains. The research confirmed the hypothesis that IMC for sustainability as an innovative business management tool fosters sustainable development. Based on the results of the research, the authors have drawn up a conceptual model of IMC for sustainable business development, and the results of the research are of both theoretical and practical value.
Keywords: M10; M14; M31; 330; integrated marketing communication; integrated marketing communication model; integrated marketing communication tools; sustainability; sustainable development